2013
DOI: 10.1111/jsm.12040
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive Treatment with Lodenafil Carbonate for Erectile Dysfunction in Outpatients with Schizophrenia and Spectrum: A Randomized, Double-Blind, Crossover, Placebo-Controlled Trial

Abstract: Introduction Evidence is accumulating to support the presence of erectile dysfunction in patients with schizophrenia. This dysregulation may be amenable to therapeutic intervention to improve adherence and quality of life of patients who suffer from schizophrenia and schizoaffective disorders. Aim We aimed to evaluate the use of adjunctive medication lodenafil for the treatment of erectile dysfunction in outpatients with schi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…According to the findings from studies on Major Depressive Disorder, mirtazapine itself may carry some sexual side effects, although estimates of their prevalence remain lower than for the majority of other antidepressants (13). However, in some studies mirtazapine demonstrated favourable effects on sexual dysfunction in depressed patients (14). Mirtazapine has also repeatedly accompanied improvements in several symptoms of sexual dysfunction caused by SSRIs (15,16), although these data remain equivocal (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the findings from studies on Major Depressive Disorder, mirtazapine itself may carry some sexual side effects, although estimates of their prevalence remain lower than for the majority of other antidepressants (13). However, in some studies mirtazapine demonstrated favourable effects on sexual dysfunction in depressed patients (14). Mirtazapine has also repeatedly accompanied improvements in several symptoms of sexual dysfunction caused by SSRIs (15,16), although these data remain equivocal (17).…”
Section: Discussionmentioning
confidence: 99%
“…Another possible strategy for improving sexual functioning in schizophrenia may be add-on treatment with mirtazapine, an antidepressant that carries a seemingly low risk of sexual dysfunction in patients with depression (13). Hypothetically, mirtazapine, an antidepressant with a serotonin 5HT-2a/c receptor blocking properties added to a pure D2 receptor blocker (i.e., FGA), may emulate the receptor profile of an SGA and, thus, improve sexual functioning (14).…”
Section: Introductionmentioning
confidence: 99%
“…27 There also is evidence that lodenafil is efficacious in the treatment of ED in men with ED and schizophrenia. 244 There were no significant differences between the lodenafil and placebo groups. Therefore, it cannot be recommended.…”
Section: Lodenafilmentioning
confidence: 91%
“…An investigation of augmentation with cabergoline in patients (n = 80) receiving a range of antipsychotics found a reduction in prolactin levels with cabergoline treatment in all patients, with mean levels of 73.3 ng/mL (±46.8) to 42.0 ng/mL (±27.8) at month 3 and 27.1 ng/mL (± =20.4) at month 6: mean total ASEX scores also declined, from 19.1 (±5.1) to 17.6 (±5.5) at month 3, and 15.0 (±6.5) at month 6 (Kalkavoura et al, 2013). Finally, a randomized, double-blind, crossover, placebo-controlled investigation of lodenafil in male patients (n = 50) with schizophrenia and erectile dysfunction found that both lodenafil and placebo were associated with an improvement in ASEX, IIEF scale, PANSS, and QLS scores, with no statistical differences between treatment groups in all sexual domains or in hormone levels (Nunes et al, 2013).…”
Section: Treatment-emergent Sexual Dysfunction During Antipsychoticmentioning
confidence: 97%
“…A number of studies have employed the ASEX scale to determine the incidence of treatment emergent sexual dysfunction during antipsychotic drug treatment (Atmaca, Kuloglu, & Tezcan, 2005;Byerly et al, 2004;Byerly, Nakonezny, & Rush, 2008;Hanssens et al, 2008;Kalkavoura et al, 2013;Konarzewska et al, 2009;Nakonezny, Byerly, & Rush, 2007;Nunes, Lacaz, Bressan, Nunes, & Mari, 2013;Uçok, Incesu, Aker, & Erkoç, 2007) (see Table 4).…”
Section: Treatment-emergent Sexual Dysfunction During Antipsychoticmentioning
confidence: 99%